PHILOSOPHICAL ANALYSIS OF THE DISCOURSE OF INFORMATION ETHICS AND ITS MORAL-PRACTICAL DILEMMAS - Shorina, Tatiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. In the context of the information revolution of the last quarter of the XX century and the transition of most developed societies from industrial to information stage, the problem of philosophical and ethical understanding of the new human situation has been actualized. The emergence of various types of applied and professional ethics has become a kind of response to this situation. Information ethics is one of these varieties. Research methods. The theory and method of discourse analysis, the method of comparative analysis, as well as system-logical, dialectic, analytical, synthetic and structural research methods are applied. The aim and tasks. The paper considers the features of information ethics. It analyses its ethical and practical nature, traces the history of its formation and designates the key moral and ethical, axiological, existential themes. Researchresults. Since the moment of informational transformations of society and the spiritual influence of postmodernism, the diversity of schools and approaches to the problems of ethics and morality has been characterized by pluralistic epistemology and ontological decentration. The possibilities of ethics as a moral philosophy are recognized as limited; therefore, a need for practical ethics arose. Applied ethics takes the role of a kind of methodology for making moral decisions in specific situations. Information ethics is a type of applied ethics and, first of all, is focused on the study of practices related to the functioning of information technology systems, world communication networks, in general, electronic culture. Its purpose is to solve dramatic, controversial, dilemma problems manifested in human relationships within information environment. Information ethics concerns not only ethical, but also social, legal and technical issues. The term "information ethics" first appeared in the library and information literature in the late 1980s, and in recent decades, it has been developing not only within, but also beyond the professional and scientific communities. Discussion. The different approaches tothe meaning of information ethics in the works of R. Capurro and L. Floridi is analyzed. R. Capurro, distinguishes the concept of "information ethics" from the close concept of "computer ethics. R. Capurro's “information ethics” acts as a generic concept, and is thought of as “the entire information and communication sphere.” L. Floridi views information ethics as an onto-centric environmental ethics; therefore, he shiftsethical regulation from society to the sphere of animate and inanimate nature. The article also discusses the dilemmas of current topics of information ethics. Conclusion. The changes associated with the rapid development of information and computer technologies not only open up enormous opportunities for humanity, but also cause the emergence of new ethical problems. Information ethics requires that the information society tobe based on the principles of mutual respect and respect for human rights.